Analysis of Construction Delay Factors on Project Quality Performance Through Quality Standards and Specifications - Diana, Lala; Amin, Mawardi (Eduvest - Journal of Universal Studies, 2025)
This study aims to examine the relationship between construction delay factors, quality standards and specifications, and quality performance of building construction projects. In addition, this study also explores the role of quality standards and specifications as a mediator in the relationship between construction delays and project quality. By using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS), this research is able to analyze complex relationships between variables that cannot be measured directly. In addition, to explore the factors that cause delays, the Root Cause Failure Analysis (RCFA) method is used to identify the root of the problem, and Failure Mode and Effect Analysis (FMEA) to analyze the risk of delays using a risk priority number (RPN). RPN is calculated based on severity, likelihood of occurrence, and detectability for each failure mode identified, prioritizing critical risks that need to be addressed immediately. The results show a very high level of significance, indicating that the delay factor plays a role in influencing project quality performance through quality standards and specifications as a mediating variable. The RCFA and FMEA methods proved effective in identifying the causes of delay and providing recommendations for corrective measures. This research contributes to construction project management by emphasizing the importance of implementing quality standards and specifications, as well as the need for systematic management of delay risks. The findings are relevant for practitioners and academics to improve efficiency and quality in the delivery of construction projects in Indonesia.